Outcome of Dynamic Hip Screw Fixation in Patients with Fractures Related to Intertrochanteric Femur - Agha Momin, Mehtab Ali Shahani, Fraz Noor, Kamran Saeed, Naeem Mehmood Mughal, Zulfiqar Ali Soomro, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the outcome of dynamic hip screw fixation in intertrochanteric femur fractures. Study Design: Prospective cohort study. Place and Duration of Study: Department of Orthopaedics, Pak Red Crescent Medical & Dental College, Dina Nath from 1st October 2020 to 31st March 2022. Methodology: Fifty Patients suffering from intertrochanteric femur fractures were enrolled. The operational time as well as incision length, measurement of blood loss during surgery was recorded. The chance of re operating on a patient and post-operative infection was also observed and documented. A complete follow up for assessing the outcomes of dynamic hip screws were continued until 18 months. Results: The mean age of the patients was 58.05±7.58 year. There were 64% males in this study while only 36% females. The ASA grade presented 32% cases within grade II while grade I and IV had equal number of cases in it. The Harris hip score presented outcome scores at 1 then 2 followed by 12 then 15 and 18 months as mean 75.37, 85.40, 88.25, 88.76 and 87.53 respectively. Conclusion: Dynamic hip screw fixation is reliable surgical procedure for treating intertrochanteric femur fractures with decreased complication rate and improved Harris hip scoring. Keywords: Proximal femoral nail technique, Distal hip, Hip fracture